Crisis intervention in the case of psychotraumatic situation - Norkina, Iryna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The article deals with the questions of the psychologist’s activity regarding assistance to the person in crisis. The basics of the theory of crisis intervention are outlined, the concept of crisis is operationalized and criteria for distinguishing between the concepts of micro trauma and micro trauma are introduced. The conceptual apparatus of the approach is developed in detail and the necessity of its unified understanding by practical psychologists is substantiated. The purpose of the article is to analyze the process of crisis intervention in the activity of the psychological service (psychologist), which takes measures to resolve the traumatic situation and reduce its impact on human life. An important factor in crisis intervention is the psychologist’s understanding of the nature of the crisis, the severity and mechanisms of its experience. An important place is given to the stages of personal response, which determines the strategy and directions of professional intervention. Analyzing the process of crisis intervention in the activities of a psychologist (psychological service) identified important tasks that should be implemented: 1) the removal of symptoms; 2) recovery to crisis level of functioning; 3) awareness of those events that lead to an imbalance; 4) identify the internal resources of the client and family in various forms of crisis management assistance. The theoretical and practical recommendations given are outlined by the use of the voyage method, based on the real case of a crisis situation, which led to psychological trauma in participants and witnesses. As the above case is related to a terrorist act, the article also provides theoretical and methodological information regarding the specificity of the work of a psychologist with the concept of terrorism and the peculiarities of its impact on participants and witnesses of such acts. Based on the results of the case study, the author formulated practical recommendations for practicing psychologists on what to consider when dealing with an injury, especially if it was caused by an act of terrorism. The article concludes with the need to take into account the emotional reactions of a person to a crisis and the long-term changes in their ability to withstand daily problems. Crucial in dealing with clients is given to the psychological conditions that are discussed in detail in the article.